Spontaneous Preterm Labor During Hemodialysis In A Patient With End-Stage Renal Disease And Advanced Maternal Age: A Case Report - Moch. Arif Rachmana; Lupita G. Laraz; Raditya Ery Pratama; Agnes Ilene Suprapto Puteri (Universitas Malahayati Lampung, 2025)
ABSTRACT Pregnancy in patients with ESRD is rare due to impaired fertility caused by HPO axis disruption. Nevertheless, with advancements in dialysis and maternal care, successful pregnancies have increasingly been reported. Such pregnancies, however, are considered high-risk and are often associated with complications such as preterm labor, intrauterine growth restriction, and low birth weight, particularly in patients with comorbidities like chronic hypertension and other risk factors such as AMA. A 41-year-old gravida 3 para 2 woman with ESRD secondary to chronic hypertension, undergoing routine hemodialysis twice weekly with each session lasting five hours for the past five years, presented with spontaneous preterm labor during a scheduled dialysis session. The patient began experiencing uterine contractions accompanied by a bloody show during the second hour of hemodialysis. The session was discontinued prematurely due to these symptoms. Subsequent examination revealed cervical dilation of 3 cm, confirming the onset of labor. Due to a history of menstrual irregularities, the pregnancy had been recognized relatively late, at 20 weeks of gestation. At 31 weeks, the patient delivered a live preterm infant. The neonate was born with low birth weight but responded well to immediate neonatal management and stabilization. Although pregnancy in ESRD patients presents significant risks, favorable maternal and neonatal outcomes can still be achieved. This case illustrates the importance of early detection, coordinated multidisciplinary care, and vigilant monitoring in improving perinatal outcomes in women undergoing chronic hemodialysis. Keywords: End-Stage Renal Disease, Hemodialysis, Preterm Labor, High Risk Pregnancy.